Grafting as a Method to Increase the Tolerance Response of Bell Pepper to Extreme Temperatures - Aidoo, M.K. (2020)
Fluctuations of winter and summer and day and night temperatures strongly influence shoot and root growth, as well as the whole plant tolerance to extreme soil temperatures. We compared the response of a commercial pepper (Capsicum annuum L.) hybrid (Romance, Rijk Zwaan) to a range of soil temperatures when grafted to a new rootstock hybrid (S101, Syngenta), self‐grafted, or ungrafted. The new rootstock hybrid was bred for enhancing abiotic stress tolerance. Plants were grown during winter and summer seasons in a plastic greenhouse with natural ventilation. Minirhizotron cameras and in‐growth cores were used to investigate grafted bell pepper root dynamics and root and shoot interactions in response to extreme (low and high air and soil) temperatures. Soil and air temperatures were measured throughout the experiment. The variations of the grafted peppers and the ungrafted aboveground biomass exposed to low and high temperatures during winter and summer were higher in the Romance grafted on the S101 rootstock than in the self‐grafted and ungrafted Romance. The plot of rootstock S101 accumulated Cl, and the rootstock efficiently allocated C into the leaves, stems, and roots and N into the leaves, stems, and fruits. These traits of rootstock S101 can be used to improve the tolerance of other pepper cultivars to low and high soil temperatures, which could lengthen the pepper growing season, as well as provide highly interesting information to plant breeders.